Women, infanticide, and the press, 1822-1922 : news narratives in England and Australia - Goc, Nicolá (Routledge, 2016)
Goc applies Critical Discourse Analysis to infanticide news in the period 1822-1922 to reveal both the broader patterns and the particular rhetorical strategies journalists in England and Australia used to report on infanticidal women. Her study is a rich and nuanced treatment of how infanticide narratives were politicized in the press and woven into narratives about the regulation of women, medicine, the law and social welfare that ultimately affected political developments like the 1834 Poor Law.